2004
DOI: 10.1111/j.1475-1305.2004.00164.x
|View full text |Cite
|
Sign up to set email alerts
|

Local Strain Measurement within Tendon

Abstract: Tendon is a dense connective tissue, responsible for transmitting the forces generated by muscles to the skeleton. It is composed of a hierarchical arrangement of crimped collagen fibres, interspersed with proteoglycan matrix and cells, known as tenocytes. During physiological loading, tendons are subjected to strains in the region of 5–6%, which result in the straightening and realignment of the collagen fibres, generating variable local strain fields within the tendon. This study demonstrates a technique for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
97
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(109 citation statements)
references
References 28 publications
(25 reference statements)
11
97
1
Order By: Relevance
“…Samples were attached to a mini materials test machine using custom clamps and tested in a PBS bath at room temperature. During pilot testing it was observed that the fascicles appeared to rotate a small amount (less than a quarter turn) during constant strain rate testing, which is consistent with previous observations [17]. Since both clamps were fixed, this was not true rotation.…”
Section: Methodssupporting
confidence: 89%
See 2 more Smart Citations
“…Samples were attached to a mini materials test machine using custom clamps and tested in a PBS bath at room temperature. During pilot testing it was observed that the fascicles appeared to rotate a small amount (less than a quarter turn) during constant strain rate testing, which is consistent with previous observations [17]. Since both clamps were fixed, this was not true rotation.…”
Section: Methodssupporting
confidence: 89%
“…Apparent rotation of the fascicles was observed during the ramping phase of tensile elongation below the transition strain, as previously observed [17]. This suggests the presence of a helical organization within the fascicle.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…For collagen in bovine pericardium, at low strain, the Poisson's ratio appears to have a very high value (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27), but for strain above 0.09, the Poisson's ratio is in the range 2.1-2.8. For the total strain (from 0 to 0.25), the change in d-spacing and diameter gives 0 ¼ 2.1 6 0.7 (these values of 0 can be calculated from Fig.…”
Section: Resultsmentioning
confidence: 95%
“…17 It has also been suggested that in tendon, the strain may be taken up by sliding of fibrils within the tendon rather than by extension of the collagen fibrils. 18 In leather, where there is very little crimp, the reorientation of fibrils may be an important mechanism for absorbing strain. 19,20 Here, the behavior of individual fibrils of collagen I as strain is applied is studied using small angle X-ray scattering (SAXS) to simultaneously measure the fibril length extension and fibril diameter contraction.…”
Section: Introductionmentioning
confidence: 99%